1997
DOI: 10.1002/elan.1140090503
|View full text |Cite
|
Sign up to set email alerts
|

Quinoprotein glucose dehydrogenase modified carbon paste electrode for the detection of phenolic compounds

Abstract: The development of an amperometric biosensor for the determination of phenolic compounds is described, using quinoprotein glucose dehydrogenase, The enzyme is integrated into carbon paste and its ability to donate electrons to oxidized phenolic compounds during glucose oxidation is exploited. The sensor response is based on electrochemical oxidation of the phenolic compound followed by its enzymatic regeneration when the bulk solution contains glucose and the electrode is potentiostated at +500 mV (vs. Ag/AgCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…Glassy carbon electrodes, which were modified by glucose oxidase [4], glucose dehydrogenase [7,17] or laccase [17] have shown good sensitivity in the relevant range with lower detection limits between 1 and 20 nmol/L. Alternatively, a carbon paste electrode incorporating glucose dehydrogenase was developed with similar sensing characteristics [18]. However, a problem is still the reproducible fabrication of such sensors and the relatively slow response rate.…”
Section: Introductionmentioning
confidence: 98%
“…Glassy carbon electrodes, which were modified by glucose oxidase [4], glucose dehydrogenase [7,17] or laccase [17] have shown good sensitivity in the relevant range with lower detection limits between 1 and 20 nmol/L. Alternatively, a carbon paste electrode incorporating glucose dehydrogenase was developed with similar sensing characteristics [18]. However, a problem is still the reproducible fabrication of such sensors and the relatively slow response rate.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, covalent immobilization could make the redox cycle of the substrate to take place on the surface very closely and minimize the diffusional resistance of the substrate. Comparatively, response times of some reported sensors for HQ are 5s, 90s and 7.5 min for laccase, 19 GDH 21 and GOD 22 immobilized sensor, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…22 The long-term stability of the sensor is 60 days for HQ with retaining 80% of initial activity. Wasa et al reported that T. versicolor laccase immobilized Epoxy-RVC sensor retained about 65% of initial activities after repetitive use for 2 months, 19 Wollenberger et al reported that response of GDH modified carbon paste electrode dropped by 50% after 10 days 21 and Lindgren et al reported that half the response remained after storage in 4 o C for 1 week for CDH sensor. 23 The very fast response and the durable long-term stability are the principal advantages of the laccase covalently immobilized sensor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that quinoprotein ADHs can be used for biotechnological applications, e.g., as biosensors or for the stereoselective oxidation of chiral alcohols (14,17,28,39,51). The broad substrate spectrum makes them useful for the production of different pure enantiomers (44).…”
mentioning
confidence: 99%